Implikasi Regulasi Cukai Hasil Tembakau (Studi Kasus Peredara n Rokok Ilegal Di Kantor Pengawasan dan Pelayanan Bea dan CukaiTipe Madya Pabean B Surakarta) - Wuryastuti, Andriyani; , Prof . Dr. Harun, SH,M,Hum; , Dr. Kelik Wardiono, SH, MH (2017)
Law No. 39 of 2007 is an amendment to Act No. 11 of 1995 on Excise. One of the changes include an increase in tobacco tax rates. With the new regulations, the government can raise budget revenue from excise duty. But on the one hand, the government's policy to raise the cigarette tax is apparently resulted in a number of cigarette factories to lower middle feel heavy and can be devastating to small tobacco companies. This resulted in the spread of illegal cigarettes peredaraan conjunction with strict regulations. Illegal distribution of cigarettes estimated to reach 4% -6% of total cigarette production reached 320-340 billion cigarettes per year in 2014. Based on data KPPBC Type Madya B Surakarta, that few companies go bankrupt the tobacco industry either because of government policy, as well as because of the defeat in the competition. The high price of raw materials for cigarettes, tobacco and cloves, coupled with a turnover or sales that do not meet the target. So based on data from 2012-2014 consequences of violations of illegal distribution of cigarettes in various brands. Some of the issues that will be discussed, the problem in this thesis, namely: a) the existence of Law Number 39 of 2007 on the Amendment of Law No. 11/1995 on Excise resulted in many illegal distribution of cigarettes in Surakarta; b) the role, functions and authority of the Office of Supervision and Customs and Excise Surakarta in handling cases of illegal cigarettes in Surakarta; and c) prevention models are ideal to suppress the circulation of illegal cigarettes, by using the method of legal research conducted by the non-doctrinal approach is qualitative. The data used in this study is data on the number of illegal distribution of cigarettes netted by KPPBC Type Madya B Surakarta in the 2012-2014 time span. The conclusions of this study: 1) Kebederadaan Act No. 39 Year 2007 on the Amendment of Law No. 11/1995 on Excise creates an enormous circulation of illegal cigarettes in Surakarta. This is shown by the escalation of the increase in the number of illegal distribution of cigarettes in Surakarta, with varied types of offenses yanf; 2) The role, functions and authority of the Office of Supervision and Customs and Excise Surakarta in dealing with cases of cigarettes illegal based on the decision of the Directorate General of Customs and Excise No. KEP 154 / BC / 2013 specified in the Circular No: SE-08 / BC / 2014 Teantang Implementation Evaluation Main Office of Customs and Excise, the Office of Customs and Excise service Madya Utama, Control and service Office Customs and Excise type Primary (Primary KPPBC) in the Directorate General of Customs and Excise Period 2014-2016; and 3) Using the proactive method of prevention models are ideal bid to suppress the illegal distribution of cigarettes. Keywords: Regulatory Implications, Excise Tobacco, Cigarettes Illegal Abstract